Technological world support in peruvian universities for management processes - Aldana Yarlequé, Cristhian Nicolás (2019)
Objective: Evaluate the characteristics of the proposal for the improvement of administrative management processes in at university institution with world-class planning systems of business resources (ERP), 2016. Method: The type of research is descriptive, quasi-experimental and transversal design was used. Two questionnaires were administered: Current processes of its administrative management and Enterprise Resource Planning Systems (ERP); also, a survey to determine the security of your information based on ISO 17799, providing data that generated a basis in SPSS v.20 processed with Factor Analysis. Results: The tools of these questionnaires were evaluated based on a pilot sample, whose Cronbach's alpha was 0.964 and 0.907 respectively, probabilities that qualify the data collection instruments as highly reliable. Next, the factorial analysis defined four factors for management and five factors for business resource planning. Conclusions: To give rise to a proposal that manages the increase level of compliance in Administrative Management and Information Security protocols, since its compliance is 11.79% and the correlations of factors identified are greater than 0.50. Indicating latent behavior patterns in workers that interrelate administrative management and planning processes and compliance with protocols.